Bifactorial structure of Locus of Control cross-culturally invariant across Spain, Chile and United Kingdom - Suárez-Álvarez, Javier (2015)
Locus of control (LOC) is an often studied variable owing to the important role it plays in different contexts. Nonetheless, there is no unanimous agreement about how many dimensions make up the factorial structure of the locus of control. The goal of this research was to add new evidence of cross cultural validity in relation to the bifactorial invariance of the LOC. The test was given to a total of 1,781 participants from Spain (697), Chile (890) and The United Kingdom (194). The study of the factorial invariance between the groups was carried out using multigroup confirmatory factor analysis models for ordered-categorical data. The progressive evaluation of factorial invariance confirms that factor loadings, thresholds and error variances are invariant across groups. Relevant cross-cultural differences in LOC between Spain, Chile, and United Kingdom were not found (PS < .50).